The Role of Accounting Information Systems in Improving the Accuracy of Budget Planning and Control in Government Agencies - Safariah, Iin; Zatnika, Yudi; Nurhasanah, Erna; Kurniasih, Nia (Journal of Economics and Management Scienties, 2025)
This study investigates the role of Accounting Information Systems (AIS) in improving the accuracy of budget planning and control within government agencies. Employing a qualitative case study approach, data were collected through semi structured interviews with financial managers, internal auditors, and system developers from multiple Indonesian public institutions. Supplementary analysis of official budgeting documents was conducted to triangulate findings. The results reveal that AIS contributes significantly to enhancing data integration and forecasting reliability, thereby reducing budget variances and supporting transparency. Furthermore, the system strengthens internal control mechanisms through real time audit trails and compliance tracking. However, the research also identifies persistent challenges, including limited technical interoperability, uneven digital infrastructure, and user competency gaps. The study emphasizes that the effectiveness of AIS is contingent upon institutional readiness, organizational culture, and sustained leadership support. A conceptual model is proposed to depict the interactive dynamics among system input, organizational processes, and budgetary outcomes. This research contributes to the literature by contextualizing AIS implementation in the public sector and highlighting its strategic relevance for fiscal governance. Implications for policy and system design are discussed, alongside suggestions for future research on AI enhanced budgeting systems.